C-X3-C motif chemokine ligand 1/receptor 1 regulates the M1 polarization and chemotaxis of macrophages after hypoxia/reoxygenation injury. Issue 4 (December 2021) - Guo, Shuiming; Dong, Lei; Li, Junhua; Chen, Yuetao; Yao, Ying; Zeng, Rui; Shushakova, Nelli; Haller, Hermann; Xu, Gang; Rong, Song
Abstract: Background: Macrophages play an important role in renal ischemia reperfusion injury, but the functional changes of macrophages under hypoxia/reoxygenation and the related mechanism are unclear and need to be further clarified. Methods: The effects of hypoxia/reoxygenation on functional characteristics of RAW264.7 macrophages were analyzed through the protein expression detection of pro-inflammatory factors TNF-α and CD80, anti-inflammatory factors ARG-1 and CD206. The functional implications of C-X3-C motif chemokine receptor 1(CX3CR1) down-regulation in hypoxic macrophages were explored using small interfering RNA technology. Significance was assessed by the parametric t -test or nonparametric Mann–Whitney test for two group comparisons, and a one-way ANOVA or the Kruskal–Wallis test for multiple group comparisons. Results: Hypoxia/reoxygenation significantly increased the protein expression of M1-related pro-inflammatory factors TNF-α, CD80 and chemokine C-X3-C motif chemokine ligand 1 (CX3CL1)/CX3CR1 and inhibited the protein expression of M2-related anti-inflammatory factors ARG-1 and CD206 in a time-dependent manner in RAW264.7 cells. However, the silencing of CX3CR1 in RAW264.7 cells using specific CX3CR1-siRNA, significantly attenuated the increase in protein expression of TNF-α ( P < 0.05) and CD80 ( P < 0.01) and the inhibition of ARG-1 ( P < 0.01) and CD206 ( P < 0.01) induced by hypoxia/reoxygenation. In addition, we also found that hypoxia/reoxygenation could significantly enhance the migration (2.2-fold, P < 0.01) and adhesion capacity (1.5-fold, P < 0.01) of RAW264.7 macrophages compared with the control group, and CX3CR1-siRNA had an inhibitory role (40% and 20% reduction, respectively). For elucidating the mechanism, we showed that the phosphorylation levels of ERK ( P < 0.01) and the p65 subunit of NF-κB ( P < 0.01) of the RAW264.7 cells in the hypoxic/reoxygenation group were significantly increased, which could be attenuated by down-regulation of CX3CR1 expression ( P < 0.01, both). ERK inhibitors also significantly blocked the effects of hypoxic/reoxygenation on the protein expression of M1-related pro-inflammatory factors TNF-α, CD80 and M2-related anti-inflammatory factors ARG-1 and CD206. Moreover, we found that conditioned medium from polarized M1 macrophages induced by hypoxia/reoxygenation, notably increased the degree of apoptosis of hypoxia/reoxygenation-induced TCMK-1 cells, and promoted the protein expression of pro-apoptotic proteins bax ( P < 0.01) and cleaved-caspase 3 ( P < 0.01) and inhibited the expression of anti-apoptotic protein bcl-2 ( P < 0.01), but silencing CX3CR1 in macrophages had a protective role. Finally, we also found that the secretion of soluble CX3CL1 in RAW264.7 macrophages under hypoxia/reoxygenation was significantly increased. Conclusions: The findings suggest that hypoxia/reoxygenation could promote M1 polarization, cell migration, and adhesion of macrophages, and that polarized macrophages induce further apoptosis of hypoxic renal tubular epithelial cells by regulating of CX3CL1/CX3CR1 signaling pathway.